Metal vulcanization compound, friction material, preparation method of friction material, brake pad, brake disc and vehicle
By using SnS·MoS2·Cu2S·Sb2S3 metal vulcanized composite in friction materials, the problems of reduced friction performance and thermal decay at high temperatures of existing friction materials are solved, and stable high-temperature friction performance and extended service life are achieved.
Patent Information
- Application Number
- CN202311416962.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
AI Technical Summary
The friction performance of existing friction materials under high temperature conditions decreases, wear increases, and cannot effectively improve the thermal fading.
A metal vulcanized composite, including SnS·MoS2·Cu2S·Sb2S3, is used as a key component of the friction material. Through specific preparation methods and formulations, the high temperature and thermal decay resistance of the friction material is improved.
The stable friction coefficient and excellent wear resistance of friction materials at high temperatures are achieved, which delays the structural damage of friction materials at high temperatures and effectively improves the thermal fading problem.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of friction materials, and in particular to a metal vulcanized composite, a friction material and a preparation method thereof, a brake pad, a brake disc and a vehicle. Background Art
[0002] In the preparation process of friction materials, graphite and sulfide are usually used as anti-friction materials. However, these sulfide materials are expensive and easily form a friction-increasing effect under high temperature conditions, resulting in reduced friction performance and increased wear of the friction material at high temperatures. At the same time, during high-temperature friction, the thermal degradation of the friction material cannot be effectively improved. Summary of the invention
[0003] In view of this, the present application provides a metal sulfide composite, a friction material and a preparation method thereof, a brake pad, a brake disc and a vehicle. The friction material prepared from the metal sulfide composite has excellent high temperature resistance and thermal decay resistance.
[0004] In a first aspect, the present application provides a metal sulfide composite, wherein the metal sulfide composite comprises, in terms of elements, Sn, Cu, Mo, Sb and S; and the metal sulfide composite has the following general formula: SnS·MoS 2 ·Cu 2 S.Sb 2 S 3 The metal sulfide comprises, in terms of metal elements, 15-35wt% Sn, 25-40wt% Mo, 10-30wt% Cu and 0-20wt% Sb.
[0005] Optionally, the metal sulfide comprises, in terms of metal elements, 30-35wt% Sn, 35-40wt% Mo, 20-25wt% Cu and 0-10wt% Sb.
[0006] Optionally, the raw materials of the metal sulfide composite include a metal inorganic salt, a sulfur source and a solvent; The metal inorganic salt includes one or more of stannous chloride dihydrate, cupric chloride dihydrate, ammonium tetrathiomolybdate, sodium molybdate, molybdenum pentachloride, antimony trichloride, sodium thiosulfate and molybdenum trioxide; The sulfur source includes one or more of sulfur, carbon sulfide and thiourea; The solvent includes one or more of ethylene glycol, ethylenediamine, ethanol, ammonia water and acetone.
[0007] Optionally, the metal inorganic salt includes stannous chloride dihydrate, cupric chloride dihydrate and molybdenum pentachloride; the mass ratio of the stannous chloride dihydrate, the cupric chloride dihydrate and the molybdenum pentachloride is 2:(1-2):(1-2).
[0008] Optionally, the method for preparing the metal sulfide composite comprises the following steps: placing the raw materials in a reactor to react at 100-250° C., and obtaining the metal sulfide composite after the reaction.
[0009] Optionally, the reaction time is 6-32 hours.
[0010] In a second aspect, the present application provides a friction material, wherein the friction material comprises the metal sulfide composite provided in the first aspect.
[0011] Optionally, the friction material comprises, by mass, 5-12 parts of a binder, 20-30 parts of reinforcing fibers, 5-20 parts of a friction modifier, and 30-50 parts of a filler; wherein the friction modifier comprises 2-6 parts of the metal sulfide composite.
[0012] Optionally, the binder includes one or more of boron-modified phenolic resin, macromolecular phenolic resin, nitrile-modified phenolic resin, cashew nut shell oil-modified phenolic resin, silicone rubber-modified phenolic resin and acrylate rubber-modified phenolic resin.
[0013] Optionally, the reinforcing fiber includes one or more of steel fiber, brass fiber, copper fiber, aramid fiber, ceramic fiber and composite mineral fiber.
[0014] Optionally, the friction modifier includes a friction-increasing material, a friction-reducing material, and a comfort modifier; The wear-increasing material includes one or more of zircon powder, alumina, magnesium oxide, wollastonite, chromite powder, iron powder, cryolite, carbon black, silicon carbide, iron powder, copper powder, and zinc stearate; The friction-reducing material includes a metal sulfide composite and graphite; The comfort regulator includes one or more of tire powder, carbon powder, nitrile rubber powder, semi-crosslinked nitrile rubber and friction powder.
[0015] Optionally, the filler includes one or more of vermiculite, mica powder, calcium oxide, titanium dioxide, calcium phosphate, zinc sulfate, iron oxide, zinc oxide, feldspar powder, corundum powder, bentonite, calcium silicate, potassium titanate, silicon dioxide, artificial graphite, expanded graphite, iron powder, copper powder, silicon powder, mullite, manganese sulfide powder, nickel-cobalt mixture and boron.
[0016] In a third aspect, the present application provides a method for preparing a friction material, the method comprising the following steps: S1, mixing and hot pressing the raw materials of the friction material to obtain a hot pressed product; S2, heat treating and curing the hot pressed product to obtain a friction material.
[0017] Optionally, in step S1, the mixing speed is 3000-8000 r / min, and the mixing time is 15-30 min.
[0018] Optionally, in step S2, the hot pressing temperature is 120-180° C., the hot pressing pressure is 10-60 MPa, and the hot pressing time is 10-30 min.
[0019] Optionally, in step S3, the heat treatment is carried out by heating in stages: first, the temperature is kept at 140-170°C for 4-6 hours, then the temperature is raised to 170-200°C for 2-4 hours, and finally the temperature is raised to 220-230°C for 6-8 hours.
[0020] In a fourth aspect, the present application provides a brake pad, which includes the friction material provided in the second aspect, or includes the friction material prepared by the method provided in the third aspect.
[0021] In a fifth aspect, the present application provides a brake disc, which includes the brake pad provided in the fourth aspect of the present application.
[0022] In a sixth aspect, the present application provides a vehicle, comprising the brake disc provided in the fifth aspect of the present application.
[0023] Through the above technical scheme, the metal sulfide composite proposed in the present application has excellent high temperature resistance and good lubrication and wear resistance. When used in friction materials, the friction materials can have a stable friction coefficient and excellent wear resistance under high temperature conditions. At the same time, it can effectively delay and prevent the structural damage of the friction materials at high temperatures, and effectively improve the thermal decay problem of the friction materials.
[0024] Other features and advantages of the present application will be described in detail in the subsequent specific implementation section. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0026] The present application provides a metal sulfide composite, which contains, in terms of elements, Sn, Cu, Mo, Sb and S; and the metal sulfide has the following general formula: SnS·MoS 2 ·Cu 2 S.Sb 2 S 3The metal sulfide contains, in terms of metal elements, 15-35wt% Sn, 25-40wt% Mo, 10-30wt% Cu and 0-20wt% Sb. The components in the metal sulfide composite material coordinate with each other to form a physical phase, and the dispersion uniformity is good. The use of the metal sulfide composite in the friction material can make the friction material still have a stable friction coefficient and wear resistance at high temperatures, because the metal sulfide composite has a stable structure at high temperatures, thereby effectively delaying the structural damage of the friction material under high temperature conditions, and effectively improving the thermal decay of the friction material.
[0027] In one embodiment of the present application, the metal sulfide preferably further comprises, in terms of metal elements, 30-35wt% Sn, 35-40wt% Mo, 20-25wt% Cu and 0-10wt% Sb. The metal sulfide with such a composition has better wear resistance and better thermal decay resistance.
[0028] In one embodiment of the present application, the raw materials of the metal sulfide composite include a metal inorganic salt, a sulfur source and a solvent. The metal inorganic salt includes at least three inorganic salts containing metals such as molybdenum, copper, tin, and antimony, which are responsible for providing metal elements; the sulfur source is responsible for providing sulfur; and the selected solvent has a good solubility for the metal inorganic salt.
[0029] In one embodiment of the present application, the metal inorganic salt includes but is not limited to at least three of stannous chloride dihydrate, cupric chloride dihydrate, ammonium tetrathiomolybdate, sodium molybdate, molybdenum pentachloride, antimony trichloride, sodium thiosulfate and molybdenum trioxide, and the average fineness is 500-2000 mesh. Further, the metal inorganic salt may preferably be stannous chloride dihydrate, cupric chloride dihydrate and molybdenum pentachloride, and the mass ratio of stannous chloride dihydrate, cupric chloride dihydrate and molybdenum pentachloride is 2: (1-2): (1-2). Specifically, the mass ratio of stannous chloride dihydrate, cupric chloride dihydrate and molybdenum pentachloride may be but is not limited to 2: 1: 1, 2: 1: 2, 2: 2: 1 or 1: 1: 1, etc. Further, the mass ratio of stannous chloride dihydrate, cupric chloride dihydrate and molybdenum pentachloride is preferably 1: 1: 1, and the friction material of the metal sulfide composite prepared by containing the metal inorganic salt of the preferred specific mass ratio has better friction performance. In one embodiment of the present application, the metal inorganic salt includes stannous chloride dihydrate, cupric chloride dihydrate, molybdenum pentachloride and antimony trichloride, and the mass ratio of stannous chloride dihydrate, cupric chloride dihydrate, molybdenum pentachloride and antimony trichloride is 2:2:2:1, 2:1:2:1 or 2:1:1:1. In another embodiment of the present application, the metal inorganic salt includes stannous chloride dihydrate, cupric chloride dihydrate and molybdenum pentachloride, and the mass ratio of stannous chloride dihydrate, cupric chloride dihydrate and molybdenum pentachloride is 1:1:1.
[0030] In one embodiment of the present application, the sulfur source includes one or more of sulfur, carbon sulfide and thiourea, preferably sulfur and thiourea. Sulfur has good dispersibility in organic solvents, thiourea has good solubility in organic solvents, and can be converted into S in organic solvents under high temperature conditions. 2- Compared with other sulfur sources, it can participate in the reaction better and there are no other impurities affecting the reaction.
[0031] In one embodiment of the present application, the solvent includes one or more of ethylene glycol, ethylenediamine, ethanol, ammonia and acetone, preferably a mixed aqueous solution of ethanol and ethylene glycol. Ethylene glycol has appropriate viscosity, good solubility, high boiling point and low saturated vapor pressure, and is generally considered to be an excellent solvent. Ethanol and ethylene glycol are mutually soluble, and can be used as a reducing agent to convert the elemental sulfur that may exist in the sulfur source into S at high temperature while dissolving the metal inorganic salt. 2- .
[0032] The present application provides a method for preparing a metal sulfide composite, which can be used to prepare a metal sulfide composite in any of the above embodiments, comprising the following steps: placing the raw materials in a reactor to react at 100-250° C., washing, drying, and crushing after the reaction to obtain the metal sulfide composite.
[0033] In one embodiment of the present application, the above raw materials are placed in a polytetrafluoroethylene reactor for reaction, and the reaction time is 6-32 hours. Further, the reaction temperature is preferably 150-200°C, and the reaction time is preferably 12-24 hours. In the present application, as the temperature rises, the reaction rate will increase; however, when the temperature is too high, the solution saturation will decrease, which is not conducive to the formation of a stable crystal structure, so 250-200°C is preferred. While ensuring the reaction rate, unstable products will not be formed due to high temperature. And ensuring a certain reaction time can ensure that the reaction is fully carried out. In one embodiment of the present application, the reaction temperature can be 160°C, 200°C or 240°C, and the reaction time can be 24 hours.
[0034] In the present application, in order to ensure that the metal inorganic salt fully participates in the reaction, an excess of sulfur source is used when synthesizing the metal sulfide composite. Therefore, the metal sulfide composite obtained after the reaction is attached with an excess of sulfur source that does not participate in the reaction. After the reaction, deionized water and anhydrous ethanol can be used for multiple washing and drying to improve the product purity of the metal sulfide composite.
[0035] The present application provides a friction material, which includes the metal sulfide compound in any of the above embodiments, or includes the metal sulfide compound prepared in any of the above embodiments. The friction material includes, by mass, 5-12 parts of a binder, 20-30 parts of reinforcing fibers, 5-20 parts of a friction modifier, and 30-50 parts of a filler. Among them, the friction modifier includes 2-6 parts of a metal sulfide compound. In one embodiment of the present application, the friction material includes, by mass, 10 parts of a binder, 20 parts of reinforcing fibers, 20 parts of a friction modifier (10 parts of a friction-increasing material, 8 parts of a friction-reducing material, and 2 parts of a comfort modifier), and 50 parts of a filler. In one embodiment of the present application, 4 parts of the metal sulfide compound are used.
[0036] In one embodiment of the present application, the binder includes but is not limited to one or more of boron-modified phenolic resin, macromolecular phenolic resin, nitrile-modified phenolic resin, cashew nut shell oil-modified phenolic resin, silicone rubber-modified phenolic resin and acrylate rubber-modified phenolic resin, with a fineness of 200-400 mesh. The use of modified phenolic resin can improve the poor heat resistance of ordinary phenolic resin itself, so that the binder has higher temperature resistance. The modified phenolic resin used in this application is a commonly used modified phenolic resin that is easily purchased on the market. Among them, the macromolecular phenolic resin has a longer molecular chain and a large molecular weight, and the molecular weight is between 10 5 -10 6 scope.
[0037] In one embodiment of the present application, the reinforcing fiber includes but is not limited to one or more of steel fiber, brass fiber, copper fiber, aramid fiber, ceramic fiber and composite mineral fiber, wherein the steel fiber has a length of 1-3 mm and a diameter of 50-80 μm, the brass fiber has a length of 1-3 mm and a diameter of 10-20 μm, the copper fiber has a length of 1.5-3 mm and a diameter of 10-30 μm, the aramid fiber has a length of 1-2 mm and a diameter of 1-2 μm, the ceramic fiber has a length of 1-3 mm and a diameter of 10-30 μm, and the composite mineral fiber has a length of 1-3.5 mm and a diameter of 3-8 μm. In one embodiment of the present application, the reinforcing fiber includes aramid fiber, and the friction material made of aramid fiber has excellent toughness and strength properties.
[0038] In one embodiment of the present application, the friction modifier includes a wear-increasing material, a wear-reducing material and a comfort modifier; the wear-increasing material can increase the friction coefficient of the friction material, and the wear-reducing material can reduce the friction coefficient of the friction material. The wear-increasing material and the wear-reducing material are used together to maintain dynamic balance and prevent the friction coefficient of the friction material from being too large or too small; the comfort modifier is used to improve the friction and wear performance of the friction material and improve the braking comfort. The wear-increasing material includes one or more of zircon powder, aluminum oxide, magnesium oxide, wollastonite, chromite powder, iron powder, cryolite, carbon black, silicon carbide, iron powder, copper powder, and zinc stearate, with a fineness of 200-300 mesh; the wear-reducing material includes metal sulfide composite and graphite, the fineness of the metal sulfide is 1000-1200 mesh, and the fineness of the graphite is 500-1000μm; the comfort modifier includes one or more of tire powder, carbon powder, nitrile rubber powder, semi-crosslinked nitrile rubber and friction powder, with a fineness of 150-300 mesh.
[0039] In one embodiment of the present application, the filler includes one or more of vermiculite, mica powder, calcium oxide, titanium dioxide, calcium phosphate, zinc sulfate, iron oxide, zinc oxide, feldspar powder, corundum powder, bentonite, calcium silicate, potassium titanate, silicon dioxide, artificial graphite, expanded graphite, iron powder, copper powder, silicon powder, mullite, manganese sulfide powder, nickel-cobalt mixture and boron, and the fineness is 800-1000 mesh.
[0040] The method for preparing the friction material comprises the following steps: S1, mixing and hot pressing the raw materials of the friction material to obtain a hot pressed product; S2, heat treating and curing the hot pressed product to obtain the friction material.
[0041] In step S1, the raw materials of the friction material are mixed uniformly, including: 5-12 parts of a binder, 20-30 parts of reinforcing fibers, 5-20 parts of a friction modifier, and 30-50 parts of a filler.
[0042] In step S1, the mixing speed is 3000-8000 r / min, and the mixing time is 15-30 min. In one embodiment of the present application, the mixing speed can be 3500 r / min, and the mixing time can be 30 min, so that the raw materials of the friction material are fully mixed.
[0043] In one embodiment of the present application, the reinforcing fibers include aramid fibers; in step S1, the aramid fibers need to be pre-opened. Since aramid fibers may be entangled with each other due to electrostatic effects, the pre-opening process can mechanically untangle most of the aramid fibers, making it easier to mix with the material and improving the uniformity of the mixture.
[0044] In step S2, the hot pressing temperature is 120-180°C, the hot pressing pressure is 10-60MPa, and the hot pressing time is 10-30min. In one embodiment of the present application, the hot pressing temperature can be 165°C, the hot pressing pressure can be 35MPa, and the hot pressing time can be 10min.
[0045] In step S3, the heat treatment is carried out by heating in stages: first, keep the temperature at 140-170°C for 4-6 hours, then heat it to 170-200°C for 2-4 hours, and finally heat it to 220-230°C for 6-8 hours. First, the binder is gradually cured at 140-200°C. If the temperature is too high, the binder will be partially cured, and all the binder will not be cured or the binder will not be cured completely; then heat it to 220-230°C, which can decompose the small molecules in the material, such as phenol or formaldehyde molecules in phenolic resin, which will be converted into gaseous state and dissipate from the material. The friction material prepared in this way can prevent the occurrence of product cracking due to poor stability of small molecules during braking.
[0046] The present application provides a brake pad, which includes the friction material in any one of the above embodiments.
[0047] The present application provides a brake disc, which includes the above-mentioned brake pad.
[0048] The present application provides a vehicle, which includes the above-mentioned brake disc.
[0049] The effect of the technical solution of this application is further illustrated below through specific examples.
[0050] Example 1 Preparation of metal sulfide composite: the metal inorganic salts used are stannous chloride dihydrate, copper chloride dihydrate, molybdenum pentachloride and antimony trichloride, with a mass ratio of 2:2:2:1; the sulfur source is a mixture of sulfur and thiourea, with a mass ratio of 1:1; the solvent is a mixed aqueous solution of ethanol and ethylene glycol, with a mass ratio of 2:1. The reaction is carried out at 200°C in a polytetrafluoroethylene reactor for 24 hours, and after the reaction, it is washed and dried with deionized water and anhydrous ethanol for many times, and crushed to obtain a metal sulfide composite; the metal sulfide composite has the following general formula: SnS·MoS 2 ·Cu 2 S.Sb 2 S 3 ; and the metal sulfide composite comprises, in terms of metal elements, 33.1 wt % Sn, 38.3 wt % Mo, 23.4 wt % Cu and 5.2 wt % Sb.
[0051] Preparation of friction material: materials are weighed by mass, including: binder: 10 parts of phenolic resin; reinforcing fiber: 13 parts of iron fiber, 2 parts of aramid fiber, 5 parts of copper-zinc fiber; wear-increasing material: 4 parts of aluminum oxide, 2 parts of zircon, 4 parts of chromite; wear-reducing material: 4 parts of graphite, 4 parts of metal sulfide composite; comfort regulator: 1 part of nitrile rubber powder, 1 part of friction powder; filler: 10 parts of magnesium oxide, 6 parts of vermiculite, 2 parts of silica powder, 8 parts of zinc oxide, 10 parts of potassium titanate, 3 parts of calcium phosphate, 5 parts of iron oxide, 2 parts of calcium hydroxide, and 4 parts of iron powder. The aramid fiber is pre-opened, and the remaining materials are mixed in a mixer at a speed of 3800 r / min for 30 minutes. The mixture is evenly mixed to obtain a mixture; the mixture is hot-pressed, and the molding temperature and molding pressure of the hot-pressing process are 165° C. and 35 MPa, and the hot-pressing time is 10 minutes to obtain a hot-pressed product; the hot-pressed product is heat-treated and cured, and the heat-treatment curing process is first kept at 140° C. for 6 hours, then heated to 180° C. for 2 hours, and finally heated to 220° C. for 6 hours to obtain a friction material containing a metal vulcanized composite.
[0052] Example 2 Preparation of metal sulfide composite: the metal inorganic salts used are stannous chloride dihydrate, copper chloride dihydrate, molybdenum pentachloride and antimony trichloride, with a mass ratio of 2:2:2:1; the sulfur source is a mixture of sulfur and thiourea, with a mass ratio of 1:1; the solvent is a mixed aqueous solution of ethanol and ethylene glycol, with a mass ratio of 2:1. The reaction is carried out in a polytetrafluoroethylene reactor at 160°C for 24 hours, and after the reaction, it is washed and dried with deionized water and anhydrous ethanol for many times, and crushed to obtain a metal sulfide composite; the metal sulfide composite has the following general formula: SnS·MoS 2 ·Cu 2 S.Sb 2 S 3 ; and the metal sulfide composite comprises, in terms of metal elements, 31.7wt% Sn, 39.8wt% Mo, 20.6wt% Cu and 7.9wt% Sb.
[0053] Preparation of friction material: materials are weighed by mass, including: binder: 10 parts of phenolic resin; reinforcing fiber: 13 parts of iron fiber, 2 parts of aramid fiber, 5 parts of copper-zinc fiber; wear-increasing material: 4 parts of aluminum oxide, 2 parts of zircon, 4 parts of chromite; wear-reducing material: 4 parts of graphite, 4 parts of metal sulfide composite; comfort regulator: 1 part of nitrile rubber powder, 1 part of friction powder; filler: 10 parts of magnesium oxide, 6 parts of vermiculite, 2 parts of silica powder, 8 parts of zinc oxide, 10 parts of potassium titanate, 3 parts of calcium phosphate, 5 parts of iron oxide, 2 parts of calcium hydroxide, and 4 parts of iron powder. The aramid fiber is pre-opened, and the remaining materials are mixed in a mixer at a speed of 3500r / min for 30min. The mixture is evenly mixed to obtain a mixture; the mixture is hot-pressed, and the molding temperature and molding pressure of the hot-pressing process are 165°C, 35MPa, and 10min to obtain a hot-pressed product; the hot-pressed product is heat-treated and cured, and the heat-treatment curing process is first kept at 140°C for 6h, then heated to 180°C for 2h, and finally heated to 220°C for 6h to obtain a friction material containing a metal vulcanized composite.
[0054] Example 3 Preparation of metal sulfide composite: the metal inorganic salts used are stannous chloride dihydrate, cupric chloride dihydrate, molybdenum pentachloride and antimony trichloride, with a mass ratio of 2:2:2:1; the sulfur source is a mixture of sulfur and thiourea, with a mass ratio of 1:1; the solvent is a mixed aqueous solution of ethanol and ethylene glycol, with a mass ratio of 2:1. The reaction is carried out in a polytetrafluoroethylene reactor at 240°C for 24 hours, and after the reaction, it is washed and dried with deionized water and anhydrous ethanol for many times, and crushed to obtain a metal sulfide composite; the metal sulfide composite has the following general formula: SnS·MoS 2 ·Cu 2 S.Sb 2 S 3 ; and the metal sulfide composite comprises, in terms of metal elements, 28.2wt% Sn, 40.8wt% Mo, 17.6wt% Cu and 13.4wt% Sb.
[0055] Preparation of friction material: materials are weighed by mass, including: binder: 10 parts of phenolic resin; reinforcing fiber: 13 parts of iron fiber, 2 parts of aramid fiber, 5 parts of copper-zinc fiber; wear-increasing material: 4 parts of aluminum oxide, 2 parts of zircon, 4 parts of chromite; wear-reducing material: 4 parts of graphite, 4 parts of metal sulfide composite; comfort regulator: 1 part of nitrile rubber powder, 1 part of friction powder; filler: 10 parts of magnesium oxide, 6 parts of vermiculite, 2 parts of silica powder, 8 parts of zinc oxide, 10 parts of potassium titanate, 3 parts of calcium phosphate, 5 parts of iron oxide, 2 parts of calcium hydroxide, and 4 parts of iron powder. The aramid fiber is pre-opened, and the remaining materials are mixed in a mixer at a speed of 3500r / min for 30min. The mixture is evenly mixed to obtain a mixture; the mixture is hot-pressed, and the molding temperature and molding pressure of the hot-pressing process are 165°C, 35MPa, and 10min to obtain a hot-pressed product; the hot-pressed product is heat-treated and cured, and the heat-treatment curing process is first kept at 140°C for 6h, then heated to 180°C for 2h, and finally heated to 220°C for 6h to obtain a friction material containing a metal vulcanized composite.
[0056] Example 4 Preparation of metal sulfide composite: the metal inorganic salts used are stannous chloride dihydrate, copper chloride dihydrate, molybdenum pentachloride and antimony trichloride, with a mass ratio of 2:1:2:1; the sulfur source is a mixture of sulfur and thiourea, with a mass ratio of 1:1; the solvent is a mixed aqueous solution of ethanol and ethylene glycol, with a mass ratio of 2:1. The reaction is carried out at 200°C in a polytetrafluoroethylene reactor for 24 hours, and after the reaction, it is washed and dried with deionized water and anhydrous ethanol for many times, and crushed to obtain a metal sulfide composite; the metal sulfide composite has the following general formula: SnS·MoS 2 ·Cu 2 S.Sb 2 S 3 ; and the metal sulfide composite comprises, in terms of metal elements, 30.7wt% Sn, 37.2wt% Mo, 16.6wt% Cu and 8.3wt% Sb.
[0057] Preparation of friction material: materials are weighed by mass, including: binder: 10 parts of phenolic resin; reinforcing fiber: 13 parts of iron fiber, 2 parts of aramid fiber, 5 parts of copper-zinc fiber; wear-increasing material: 4 parts of aluminum oxide, 2 parts of zircon, 4 parts of chromite; wear-reducing material: 4 parts of graphite, 4 parts of metal sulfide composite; comfort regulator: 1 part of nitrile rubber powder, 1 part of friction powder; filler: 10 parts of magnesium oxide, 6 parts of vermiculite, 2 parts of silica powder, 8 parts of zinc oxide, 10 parts of potassium titanate, 3 parts of calcium phosphate, 5 parts of iron oxide, 2 parts of calcium hydroxide, and 4 parts of iron powder. The aramid fiber is pre-opened, and the remaining materials are mixed in a mixer at a speed of 3500r / min for 30min. The mixture is evenly mixed to obtain a mixture; the mixture is hot-pressed, and the molding temperature and molding pressure of the hot-pressing process are 165°C, 35MPa, and 10min to obtain a hot-pressed product; the hot-pressed product is heat-treated and cured, and the heat-treatment curing process is first kept at 140°C for 6h, then heated to 180°C for 2h, and finally heated to 220°C for 6h to obtain a friction material containing a metal vulcanized composite.
[0058] Example 5 Preparation of metal sulfide composite: the metal inorganic salts used are stannous chloride dihydrate, copper chloride dihydrate, molybdenum pentachloride and antimony trichloride, with a mass ratio of 2:1:1:1; the sulfur source is a mixture of sulfur and thiourea, with a mass ratio of 1:1; the solvent is a mixed aqueous solution of ethanol and ethylene glycol, with a mass ratio of 2:1. The reaction is carried out at 200°C in a polytetrafluoroethylene reactor for 24 hours, and after the reaction, it is washed and dried with deionized water and anhydrous ethanol for many times, and crushed to obtain a metal sulfide composite; the metal sulfide composite has the following general formula: SnS·MoS 2 ·Cu 2 S.Sb 2 S 3 ; and the metal sulfide composite comprises, in terms of metal elements, 34.5wt% Sn, 27.6wt% Mo, 12.7wt% Cu and 7.7wt% Sb.
[0059] Preparation of friction material: materials are weighed by mass, including: binder: 10 parts of phenolic resin; reinforcing fiber: 13 parts of iron fiber, 2 parts of aramid fiber, 5 parts of copper-zinc fiber; wear-increasing material: 4 parts of aluminum oxide, 2 parts of zircon, 4 parts of chromite; wear-reducing material: 4 parts of graphite, 4 parts of metal sulfide composite; comfort regulator: 1 part of nitrile rubber powder, 1 part of friction powder; filler: 10 parts of magnesium oxide, 6 parts of vermiculite, 2 parts of silica powder, 8 parts of zinc oxide, 10 parts of potassium titanate, 3 parts of calcium phosphate, 5 parts of iron oxide, 2 parts of calcium hydroxide, and 4 parts of iron powder. The aramid fiber is pre-opened, and the remaining materials are mixed in a mixer at a speed of 3500r / min for 30min. The mixture is evenly mixed to obtain a mixture; the mixture is hot-pressed, and the molding temperature and molding pressure of the hot-pressing process are 165°C, 35MPa, and 10min to obtain a hot-pressed product; the hot-pressed product is heat-treated and cured, and the heat-treatment curing process is first kept at 140°C for 6h, then heated to 180°C for 2h, and finally heated to 220°C for 6h to obtain a friction material containing a metal vulcanized composite.
[0060] Example 6 a. Preparation of metal sulfide composite: The metal inorganic salts used are stannous chloride dihydrate, cupric chloride dihydrate and molybdenum pentachloride in a mass ratio of 1:1:1; the sulfur source is a mixture of sulfur and thiourea in a mass ratio of 1:1; the solvent is a mixed aqueous solution of ethanol and ethylene glycol in a mass ratio of 2:1. The reaction is carried out in a polytetrafluoroethylene reactor at 200°C for 24 hours, and after the reaction, it is washed and dried with deionized water and anhydrous ethanol for many times, and crushed to obtain a metal sulfide composite; the metal sulfide composite has the following general formula: SnS·MoS 2 ·Cu 2 S; and the metal sulfide composite comprises, in terms of metal elements, 36.7wt% Sn, 40.9wt% Mo, and 22.4wt% Cu.
[0061] b. Preparation of friction materials: weigh the materials by mass, including: binder: 10 parts of phenolic resin; reinforcing fiber: 13 parts of iron fiber, 2 parts of aramid fiber, 5 parts of copper-zinc fiber; wear-increasing material: 4 parts of aluminum oxide, 2 parts of zircon, 4 parts of chromite; wear-reducing material: 4 parts of graphite, 4 parts of metal sulfide composite; comfort regulator: 1 part of nitrile rubber powder, 1 part of friction powder; filler: 10 parts of magnesium oxide, 6 parts of vermiculite, 2 parts of silica powder, 8 parts of zinc oxide, 10 parts of potassium titanate, 3 parts of calcium phosphate, 5 parts of iron oxide, 2 parts of calcium hydroxide, and 4 parts of iron powder. The aramid fiber is pre-opened, and the remaining materials are mixed in a mixer at a speed of 3500r / min for 30min. The mixture is evenly mixed to obtain a mixture; the mixture is hot-pressed, and the molding temperature and molding pressure of the hot-pressing process are 165°C, 35MPa, and 10min to obtain a hot-pressed product; the hot-pressed product is heat-treated and cured, and the heat-treatment curing process is first kept at 140°C for 6h, then heated to 180°C for 2h, and finally heated to 220°C for 6h to obtain a friction material containing a metal vulcanized composite.
[0062] Example 7 a. Preparation of metal sulfide composite: the metal inorganic salts used are stannous chloride dihydrate, cupric chloride dihydrate, molybdenum pentachloride and antimony trichloride, with a mass ratio of 2:2:1:1; the sulfur source is a mixture of sulfur and thiourea, with a mass ratio of 1:1; the solvent is a mixed aqueous solution of ethanol and ethylene glycol, with a mass ratio of 2:1. The reaction is carried out at 200°C in a polytetrafluoroethylene reactor for 24 hours, and after the reaction, it is washed and dried with deionized water and anhydrous ethanol for many times, and crushed to obtain a metal sulfide composite; the metal sulfide composite has the following general formula: SnS·MoS2·Cu2S·Sb2S3; and the metal sulfide composite contains, in terms of metal elements: 27.1wt% Sn, 28.9wt% Mo, 24.6wt% Cu and 6.6wt% Sb.
[0063] b. Preparation of friction materials: weigh the materials by mass, including: binder: 10 parts of phenolic resin; reinforcing fiber: 13 parts of iron fiber, 2 parts of aramid fiber, 5 parts of copper-zinc fiber; wear-increasing material: 4 parts of aluminum oxide, 2 parts of zircon, 4 parts of chromite; wear-reducing material: 4 parts of graphite, 4 parts of metal sulfide composite; comfort regulator: 1 part of nitrile rubber powder, 1 part of friction powder; filler: 10 parts of magnesium oxide, 6 parts of vermiculite, 2 parts of silica powder, 8 parts of zinc oxide, 10 parts of potassium titanate, 3 parts of calcium phosphate, 5 parts of iron oxide, 2 parts of calcium hydroxide, and 4 parts of iron powder. The aramid fiber is pre-opened, and the remaining materials are mixed in a mixer at a speed of 3500r / min for 30min. The mixture is evenly mixed to obtain a mixture; the mixture is hot-pressed, and the molding temperature and molding pressure of the hot-pressing process are 165°C, 35MPa, and 10min to obtain a hot-pressed product; the hot-pressed product is heat-treated and cured, and the heat-treatment curing process is first kept at 140°C for 6h, then heated to 180°C for 2h, and finally heated to 220°C for 6h to obtain a friction material containing a metal vulcanized composite.
[0064] Comparative Example 1 The metal sulfide is molybdenum disulfide.
[0065] Preparation of friction materials: Materials are weighed by mass, including: binder: 10 parts of phenolic resin; reinforcing fibers: 13 parts of iron fiber, 2 parts of aramid fiber, 5 parts of copper-zinc fiber; wear-increasing materials: 4 parts of aluminum oxide, 2 parts of zircon, 4 parts of chromite; wear-reducing materials: 4 parts of graphite, 4 parts of metal sulfide; comfort regulator: 1 part of nitrile rubber powder, 1 part of friction powder; fillers: 10 parts of magnesium oxide, 6 parts of vermiculite, 2 parts of silica powder, 8 parts of zinc oxide, 10 parts of potassium titanate, 3 parts of calcium phosphate, 5 parts of iron oxide, 2 parts of calcium hydroxide, and 4 parts of iron powder. The aramid fiber is pre-opened, and the remaining materials are mixed in a mixer at a speed of 3500r / min for 30min. The mixture is evenly mixed to obtain a mixture; the mixture is hot-pressed, and the molding temperature and molding pressure of the hot-pressing process are 165°C, 35MPa, and 10min to obtain a hot-pressed product; the hot-pressed product is heat-treated and cured, and the heat-treatment curing process is first kept at 140°C for 6h, then heated to 180°C for 2h, and finally heated to 220°C for 6h to obtain a friction material containing metal sulfide.
[0066] Comparative Example 2 The metal sulfide is tin sulfide.
[0067] Preparation of friction materials: Materials are weighed by mass, including: binder: 10 parts of phenolic resin; reinforcing fibers: 13 parts of iron fiber, 2 parts of aramid fiber, 5 parts of copper-zinc fiber; wear-increasing materials: 4 parts of aluminum oxide, 2 parts of zircon, 4 parts of chromite; wear-reducing materials: 4 parts of graphite, 4 parts of metal sulfide; comfort regulator: 1 part of nitrile rubber powder, 1 part of friction powder; fillers: 10 parts of magnesium oxide, 6 parts of vermiculite, 2 parts of silica powder, 8 parts of zinc oxide, 10 parts of potassium titanate, 3 parts of calcium phosphate, 5 parts of iron oxide, 2 parts of calcium hydroxide, and 4 parts of iron powder. The aramid fiber is pre-opened, and the remaining materials are mixed in a mixer at a speed of 3500r / min for 30min. The mixture is evenly mixed to obtain a mixture; the mixture is hot-pressed, and the molding temperature and molding pressure of the hot-pressing process are 165°C, 35MPa, and 10min to obtain a hot-pressed product; the hot-pressed product is heat-treated and cured, and the heat-treatment curing process is first kept at 140°C for 6h, then heated to 180°C for 2h, and finally heated to 220°C for 6h to obtain a friction material containing metal sulfide.
[0068] Comparative Example 3 The metal sulfide is antimony sulfide.
[0069] Preparation of friction materials: Materials are weighed by mass, including: binder: 10 parts of phenolic resin; reinforcing fibers: 13 parts of iron fiber, 2 parts of aramid fiber, 5 parts of copper-zinc fiber; wear-increasing materials: 4 parts of aluminum oxide, 2 parts of zircon, 4 parts of chromite; wear-reducing materials: 4 parts of graphite, 4 parts of metal sulfide; comfort regulator: 1 part of nitrile rubber powder, 1 part of friction powder; fillers: 10 parts of magnesium oxide, 6 parts of vermiculite, 2 parts of silica powder, 8 parts of zinc oxide, 10 parts of potassium titanate, 3 parts of calcium phosphate, 5 parts of iron oxide, 2 parts of calcium hydroxide, and 4 parts of iron powder. The aramid fiber is pre-opened, and the remaining materials are mixed in a mixer at a speed of 3500r / min for 30min. The mixture is evenly mixed to obtain a mixture; the mixture is hot-pressed, and the molding temperature and molding pressure of the hot-pressing process are 165°C, 35MPa, and 10min to obtain a hot-pressed product; the hot-pressed product is heat-treated and cured, and the heat-treatment curing process is first kept at 140°C for 6h, then heated to 180°C for 2h, and finally heated to 220°C for 6h to obtain a friction material containing metal sulfide.
[0070] Comparative Example 4 The metal sulfide is a mixture of molybdenum disulfide, tin sulfide and copper sulfide (mass ratio is 1:1:1).
[0071] Preparation of friction materials: Materials are weighed by mass, including: binder: 10 parts of phenolic resin; reinforcing fibers: 13 parts of iron fiber, 2 parts of aramid fiber, 5 parts of copper-zinc fiber; wear-increasing materials: 4 parts of aluminum oxide, 2 parts of zircon, 4 parts of chromite; wear-reducing materials: 4 parts of graphite, 4 parts of metal sulfide; comfort regulator: 1 part of nitrile rubber powder, 1 part of friction powder; fillers: 10 parts of magnesium oxide, 6 parts of vermiculite, 2 parts of silica powder, 8 parts of zinc oxide, 10 parts of potassium titanate, 3 parts of calcium phosphate, 5 parts of iron oxide, 2 parts of calcium hydroxide, and 4 parts of iron powder. The aramid fiber is pre-opened, and the remaining materials are mixed in a mixer at a speed of 3500r / min for 30min. The mixture is evenly mixed to obtain a mixture; the mixture is hot-pressed, and the molding temperature and molding pressure of the hot-pressing process are 165°C, 35MPa, and 10min to obtain a hot-pressed product; the hot-pressed product is heat-treated and cured, and the heat-treatment curing process is first kept at 140°C for 6h, then heated to 180°C for 2h, and finally heated to 220°C for 6h to obtain a friction material containing a metal vulcanized composite.
[0072] Comparative Example 5 a. Preparation of metal sulfide composites: The metal inorganic salts used are stannous chloride dihydrate, cupric chloride dihydrate, molybdenum pentachloride and antimony trichloride, with a mass ratio of 2.5:1:2.5:1; the sulfur source is a mixture of sulfur and thiourea, with a mass ratio of 1:1; the solvent is a mixed aqueous solution of ethanol and ethylene glycol, with a mass ratio of 2:1. The reaction is carried out in a polytetrafluoroethylene reactor at 200°C for 24 hours, and after the reaction, it is washed and dried with deionized water and anhydrous ethanol for many times, and then crushed to obtain a metal sulfide composite; the metal sulfide composite has the following general formula: SnS·MoS 2 ·Cu 2 S.Sb 2 S 3 ; and the metal sulfide composite comprises, in terms of metal elements, 47.7wt% Sn, 21.4wt% Mo, 34.2wt% Cu and 2.3wt% Sb.
[0073] b. Preparation of friction materials: weigh the materials by mass, including: binder: 10 parts of phenolic resin; reinforcing fiber: 13 parts of iron fiber, 2 parts of aramid fiber, 5 parts of copper-zinc fiber; wear-increasing material: 4 parts of aluminum oxide, 2 parts of zircon, 4 parts of chromite; wear-reducing material: 4 parts of graphite, 4 parts of metal sulfide; comfort regulator: 1 part of nitrile rubber powder, 1 part of friction powder; filler: 10 parts of magnesium oxide, 6 parts of vermiculite, 2 parts of silica powder, 8 parts of zinc oxide, 10 parts of potassium titanate, 3 parts of calcium phosphate, 5 parts of iron oxide, 2 parts of calcium hydroxide, and 4 parts of iron powder. The aramid fiber is pre-opened, and the remaining materials are mixed in a mixer at a speed of 3500r / min for 30min. The mixture is evenly mixed to obtain a mixture; the mixture is hot-pressed, and the molding temperature and molding pressure of the hot-pressing process are 165°C, 35MPa, and 10min to obtain a hot-pressed product; the hot-pressed product is heat-treated and cured, and the heat-treatment curing process is first kept at 140°C for 6h, then heated to 180°C for 2h, and finally heated to 220°C for 6h to obtain a friction material containing a metal vulcanized composite.
[0074] Performance Testing (1) Friction material physical properties test Four-point bending strength (4PB) uses a universal testing machine to perform a four-point bending test on the material, testing 5 sets of data and taking the average value as the test result. Density and open porosity are tested using the Archimedes drainage method.
[0075] Table 1 Friction material physical properties test data
[0076] (2) Friction material friction coefficient test The friction coefficient of the friction material under different temperature conditions was tested using an MFT-5000 constant speed friction and wear tester in accordance with standard GB 5763-2008 at a pressure of 0.98 MPa.
[0077] Table 2 Friction coefficient test data of friction materials
[0078] (3) Friction material wear test The friction and wear performance at different temperatures was tested using an MFT-5000 constant speed friction and wear tester in accordance with standard GB 5763-2008 at a pressure of 0.98 MPa. The wear rate was calculated by testing the thickness change before and after friction.
[0079] Table 3 Friction material wear test data
[0080] The physical properties of the prepared friction material were tested according to Table 1. The values of PB in Example 4 and Comparative Example 4 were both between 25-40 MPa, the density was between 3.1-3.4, and the porosity was between 10.5%-15%, indicating that the friction materials prepared in Example 4 and Comparative Example 4 had good basic properties and high repeatability.
[0081] It can be found from the test of the friction coefficient of the friction material in Table 2 that the stability of the friction coefficient of each embodiment at different temperatures is better than that of each comparative example. The average deviation in Table 2 is the average value of the absolute value of the difference between the friction coefficient at each temperature and the average friction coefficient, which can reflect the stability of the friction coefficient.
[0082] It can be found that the average wear rate of each embodiment is lower than that of each comparative example by testing the wear of the friction material through Table 3. It can be found that the friction coefficient stability of each embodiment is better than that of each comparative example and the wear is relatively lower, because the prepared metal sulfide composite has high dispersion uniformity, and the friction material prepared from the metal sulfide composite has stable friction performance and good friction and wear performance under high or low temperature conditions.
[0083] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. A metal sulfide composite, characterized in that: The metal sulfide composite comprises, in terms of elements: Sn, Cu, Mo, Sb and S; and the metal sulfide composite has the following general formula: SnS·MoS2·Cu2S·Sb2S3; the metal sulfide composite comprises, in terms of metal elements: 15-35wt% Sn, 25-40wt% Mo, 10-30wt% Cu, 0-20wt% Sb.
2. The metal sulfide composite according to claim 1, characterized in that The metal sulfide composite comprises, in terms of metal elements, 30-35 wt % Sn, 35-40 wt % Mo, 20-25 wt % Cu, and 0-10 wt % Sb.
3. The metal sulfide composite according to claim 1, characterized in that The raw materials include metal inorganic salts, sulfur sources and solvents; The metal inorganic salt includes at least three of stannous chloride dihydrate, cupric chloride dihydrate, ammonium tetrathiomolybdate, sodium molybdate, molybdenum pentachloride, antimony trichloride, sodium thiosulfate and molybdenum trioxide; The sulfur source includes one or more of sulfur, carbon sulfide and thiourea; The solvent includes one or more of ethylene glycol, ethylenediamine, ethanol, ammonia water and acetone.
4. The metal sulfide composite according to claim 3, characterized in that The metal inorganic salt includes stannous chloride dihydrate, cupric chloride dihydrate and molybdenum pentachloride; the mass ratio of the stannous chloride dihydrate, the cupric chloride dihydrate and the molybdenum pentachloride is 2:(1-2):(1-2).
5. A method for preparing the metal sulfide composite according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: placing the raw materials in a reaction kettle to react at 100-250° C., and obtaining the metal sulfide composite after the reaction.
6. The method for preparing the metal sulfide composite according to claim 5, characterized in that: The reaction time is 6-32 hours.
7. A friction material, characterized in that: The invention comprises the metal sulfide composite according to any one of claims 1 to 4, or the metal sulfide composite prepared by the method according to any one of claims 5 to 6.
8. The friction material according to claim 7, characterized in that: The invention comprises, by weight: 5-12 parts of a binder, 20-30 parts of reinforcing fibers, 5-20 parts of a friction modifier, and 30-50 parts of a filler; wherein the friction modifier comprises 2-6 parts of the metal sulfide composite.
9. The friction material according to claim 7, characterized in that: The binder includes one or more of boron-modified phenolic resin, macromolecular phenolic resin, nitrile-modified phenolic resin, cashew nut shell oil-modified phenolic resin, silicone rubber-modified phenolic resin and acrylate rubber-modified phenolic resin.
10. The friction material according to claim 7, characterized in that: The reinforcing fibers include one or more of steel fibers, brass fibers, copper fibers, aramid fibers, ceramic fibers and composite mineral fibers.
11. The friction material according to claim 7, characterized in that: The friction modifier includes a friction-increasing material, a friction-reducing material and a comfort modifier; The abrasive material includes one or more of zircon powder, alumina, magnesium oxide, wollastonite, chromite powder, iron powder, cryolite, carbon black, silicon carbide, iron powder, copper powder, and zinc stearate; The friction-reducing material includes a metal sulfide composite and graphite; The comfort regulator includes one or more of tire powder, carbon powder, nitrile rubber powder, semi-crosslinked nitrile rubber and friction powder.
12. The friction material according to claim 7, characterized in that: The filler includes one or more of vermiculite, mica powder, calcium oxide, titanium dioxide, calcium phosphate, zinc sulfate, iron oxide, zinc oxide, feldspar powder, corundum powder, bentonite, calcium silicate, potassium titanate, silicon dioxide, artificial graphite, expanded graphite, iron powder, copper powder, silicon powder, mullite, manganese sulfide powder, nickel-cobalt mixture and boron.
13. A method for preparing a friction material, characterized in that: The method comprises the following steps: S1, mixing and hot pressing the raw materials of the friction material according to any one of claims 7 to 12 to obtain a hot pressed product; S2, heat treating and curing the hot pressed product to obtain the friction material.
14. The method for preparing the friction material according to claim 13, characterized in that: In the step S1, the mixing speed is 3000-8000 r / min, and the mixing time is 15-30 min.
15. The method for preparing the friction material according to claim 13, characterized in that: In the step S2, the temperature of the hot pressing is 120-180°C, the pressure of the hot pressing is 10-60MPa, and the time of the hot pressing is 10-30min.
16. The method for preparing the friction material according to claim 13, characterized in that: In step S3, the heat treatment is carried out by heating in stages: first, the temperature is kept at 140-170°C for 4-6 hours, then the temperature is raised to 170-200°C for 2-4 hours, and finally the temperature is raised to 220-230°C for 6-8 hours.
17. A brake pad, characterized in that: The brake pad comprises the friction material described in any one of claims 7 to 12, or the friction material prepared by the method described in any one of claims 13 to 16.
18. A brake disc, characterized in that: The brake disc comprises the brake pad according to claim 17.
19. A vehicle, characterized in that: The vehicle comprises the brake disc of claim 18.